ENGLISH GEOGRAPHICAL TOPONYMS AND REASONS OF THEIR DERIVATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Historical and cultural geographers have a long research tradition of studying place names, or toponyms (topos: place, onomia: name). However, this topic is by no means the exclusive domain of geographers. Place names research has attracted the interest of archaeologists, anthropologists, historians, folklorists, cartographers, linguists, sociologists, planners, poets, and members of the general public with knowledge of the subject. Place names are fascinating because they offer vital clues and insights into the history of the landscape, the patterns and origins of settlement, the physical geography of locations, the physical geographies of subsequent occupancies, nationalistic sentiments, political and ethnic shifts, human activity, and the processes of cultural diffusion.